Alliance for Social Enterprise: A Framework to Develop Social Entrepreneurship in Emerging Economies - Harris, Dawn; Derdak, Thomas; Lash, Nicholas; Uygur, Ugur; Welch, Michael; Tuncay Zayer, Linda (Senate Hall, 2013)
This research proposes a novel framework, an alliance for social enterprise, as a model for developing social entrepreneurial initiatives in emerging economies. The alliance for social enterprise levrages the alliance partner's strengths to accomplish a social mission. The non-governmental organization (NGO) has an understanding of the local conditions and offers financial and social capital; the university utilizes its research efforts to assess the processes and enhance the positive outcomes of the strategic venture; the corporation utilizes its financial capital and provides market access to the local business; and the local business provides human capital as well as products. This strategic alliance encourages long-term sustainability with economic returns and advocates social development goals. In this research, a Coffee Cooperative in Tanzania serves as an illustrative example that demonstrates the formation and operation of the alliance for social enterprise. Keywords: Social Entrepreneurship, Strategic Alliance, Emerging Economies, Africa, Small Business
Keywords: social entrepreneurship|strategic alliance|emerging economies|Africa|small business